Unidad permanente de justicia Barrio Paloquemao: "Plan parcial Parque Judicial" (2016)
Through an analysis in the environment in which the partial plan will be located is the deterioration of different areas that have defined activities and have been used recently as scavengers like the public space is not defined and deals illegally by vehicles and trade. The current use of this area is so industrial trucks pollute space and there is a natural mantle that can counteract the pollution that occurs generating bad image in the sector.